2021
DOI: 10.1089/cyber.2020.0483
|View full text |Cite
|
Sign up to set email alerts
|

Ready or Not for Contact Tracing? Investigating the Adoption Intention of COVID-19 Contact-Tracing Technology Using an Extended Unified Theory of Acceptance and Use of Technology Model

Abstract: To diminish the risk of spreading COVID-19 as society exits the lockdowns, several apps have been developed for contact tracing. These apps register which users have been in proximity of each other. If a user is diagnosed with COVID-19, app users who have been recently in proximity to this person are notified. The effectiveness of these apps highly depends on public support. Therefore, this study investigated the factors that influence app use intention, based on an extended unified theory of acceptance and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
190
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(205 citation statements)
references
References 30 publications
10
190
2
3
Order By: Relevance
“…According to this model, users are more likely to share personal information when the benefits of the transaction outweigh the risks (Dinev & Hart, 2006), such as in the present case, when the perceived health benefits are higher than the perceived risk of data misuse (Hassandoust et al, 2020). Notably, previous research on app adoption reveals that both perceptions about the effectiveness of the app as a public health measure and about data misuse play an important role in the adoption process (Bachtiger et al, 2020;Hassandoust et al, 2020;O'Callaghan et al, 2020;Walrave et al, 2020;Wyl, Höglinger, et al, 2020).…”
Section: A Typology Of App Adoptionmentioning
confidence: 78%
See 1 more Smart Citation
“…According to this model, users are more likely to share personal information when the benefits of the transaction outweigh the risks (Dinev & Hart, 2006), such as in the present case, when the perceived health benefits are higher than the perceived risk of data misuse (Hassandoust et al, 2020). Notably, previous research on app adoption reveals that both perceptions about the effectiveness of the app as a public health measure and about data misuse play an important role in the adoption process (Bachtiger et al, 2020;Hassandoust et al, 2020;O'Callaghan et al, 2020;Walrave et al, 2020;Wyl, Höglinger, et al, 2020).…”
Section: A Typology Of App Adoptionmentioning
confidence: 78%
“…2020; Sharma et al, 2020;Walrave et al, 2020), we will not predict app adoption but describe the distinct types of app adopters with regard to their perceptions about app-related benefits and costs, their knowledge about data handling in technology, and their app-related opinion leadership. The quantitative description along these dimensions will result in unique profiles for different types of adopters.…”
mentioning
confidence: 99%
“…Table 1 shows the main forms of fear in different sectors along with the model adopted [12]. The other perspective is held by [22] where they aim to examine the impact that track-technology on a population from 18 to 64 years old. Accordingly, they aim to study the usability of such technology in tracking people who have COVID-19 symptoms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is worth to mention that what sets this paper apart from previous studies during the spread of COVID-19 [2,11,19,20] is the fact that this paper adopts a hybrid model where TAM an VAM are integrated to measure the acceptance of technology in educational environment. Other papers such as [12,21,22] are implemented in non-educational environment, which implies that it has no relation with students' perceptions or attitudes. This paper covers this where the perception and attitudes of Arab learners are the focus of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in the German context, Trang et al [34] found that appeals to the societal rather than personal benefit of contact tracing apps were most helpful to maximize uptake, particularly if the majority of the population was critical of the apps or undecided about using them. Other survey studies on the willingness to use contact tracing apps indicated that perceived benefit, expected performance, trust in government, and social influence were important motivating factors for using contact tracing apps, whereas privacy concerns were identified as the main hindering factor [8,[35][36][37][38][39][40]. In line with these surveys, Keshet [41] identified a dichotomy in the comments related to Israeli news websites between supporters of contact tracing apps who see them as a protective measure for containment and opponents who see their civil rights violated.…”
Section: Introductionmentioning
confidence: 99%